A new species of Piptolepis (Lychnophorinae, Vernonieae, Asteraceae) from the Brazilian Central Plateau - de A. Bringel Jr., João Bernardo; Cândido, Jacqueline Bonfim E; Loeuille, Benoît (Phytotaxa, 2019)
Piptolepis rosmarinifolia, a new species from Brazil, is here described and illustrated, and its conservation status assessed. The new species is endemic to the Maranhão River Plateau in the state of Goiás, Brazil. Piptolepis rosmarinifolia is closely related to P. pabstii but differs by its smaller and linear to very narrow elliptic densely spiraled leaves, solitary terminal syncephalium, a higher number of heads per syncephalium and triseriate pappus.